Chronic stress triggers impairments of the redox status of salivary glands associated with different histological responses in rats - Souza-Monteiro, Deiweson; Aragão, Walessa Alana Bragança; Né, Yago Gecy de Sousa; Mendes, Paulo Fernando Santos; Chaves-Neto, Antonio Hernandes [UNESP]; Amado, Lílian Lund; Lima, Rafael Rodrigues (Taylor & Francis, 2025)
Stress occurs as a reaction to mental and emotional pressure, anxiety, or scarring. Chronic stress is defined as constant submission to these moments. It can affect several body systems, increase blood pressure, and weaken immunity, thereby interfering with physiological health processes. Thus, this study aims to evaluate the effects of chronic stress on the redox status and histomorphological parameters of salivary glands. Thirty-two albino Wistar male rats were randomly divided into two groups: chronic stress and control. Chronically stressed animals were subjected to a restraint protocol by introducing them into a polyvinyl tube for 4 hours daily for 28 days, allowing immobilization of their movements. Subsequently, the animals were euthanized for further collection of the parotid and submandibular salivary glands. The redox state of the glands was evaluated using the antioxidant capacity against peroxyl radicals (ACAP) and thiobarbituric acid reactive substances (TBARS) assays. Histological analysis was performed through morphometry of the tissues stained with hematoxylin and eosin and histochemical through picrosirius red staining. Both the parotid and submandibular glands of stressed rats exhibited oxidative stress due to a decrease in ACAP and an increase in TBARS levels. However, the parotid glands are more susceptible to harmful changes in the tissue, such as an increase in the stromal area and in the collagen area fraction, decrease in the acinar area, and smaller size of the acinus and ducts. Our results suggest that chronic stress may cause harmful modulation of the redox state of the salivary glands, with different histological repercussions.
Keywords: Chronic stress; histomorphometric; oxidative stress; physical immobilization; PicroSirius Red; salivary glands